A review of electromagnetic processing of materials (EPM): Heating, sintering, joining and forming. (10th April 2021) - Biesuz, Mattia; Saunders, Theo; Ke, Daoyao; Reece, Michael J.; Hu, Chungfeng; Grasso, Salvatore
Abstract: Electricity is an efficient form of energy, and the growing interest in electricity-assisted manufacturing is motivated by its inherent energy saving and reduced environmental impact. Beyond this, Electromagnetic Processing of Materials (EPM) allows the fabrication of materials with new compositions, metastable phases and nanograined microstructures that cannot be obtained using conventional heating processes using furnaces. This review covers EPM for the manufacture of ceramic and metal bulk components, with a specific focus on the effects of electric fields and electromagnetic radiations on processing in a wide spectrum of frequencies ranging from DC ( f =0 Hz) to visible light ( f = 10 14 –10 15 Hz). The manuscript is divided into two parts. The first part provides a comprehensive overview of the interactions between matter and electric field/current, including heating phenomena (resistive Joule, induction, dielectric heating, electric arcs) and athermal effects (electromigration, electroplasticity, electrochemical reactions, ponderomotive force and others). The second part is focused on the technological application of the techniques, covering heat treatments, joining, sintering and forming. Seven distinct physical phenomena are involved in EPM: resistive Joule and induction heating, electrochemical reactions, electroplasticity, electric arcs and electromagnetic heating based on radio and microwave frequencies (mainly used for heating dielectric materials; i.e., dielectric heating) or on the IR/visible light (IR heating and lasers).